TRIAL WITH PARTICIPATION OF THE JURY IN THE REPUBLIC OF KAZAKHSTAN - S. Shaikenova (Russian Journal of Economics and Law)
The author views the issues connected with the jury trial functioning in Kazakhstan, as well as with finding optimal ways of for the further development and improving of this legal institution.